Right ventricular strain for prediction of mortality in patients with preserved ejection fraction. (25th November 2020) - Rothschild, E; Baruch, G.N; Kaplan, A; Kapusta, L; Topilsky, Y
Abstract: Introduction: Right Ventricular (RV) dysfunction is highly prevalent and has major prognostic implication in patients with Heart Failure (HF) with Preserved Ejection Fraction (HFpEF). Different functional indices have been proposed to evaluate RV function, most common are TEI-index, TAPSE and RVFAC%. Recent works suggested that 2-dimensional speckle tracking echocardiography (2DSTE) for RV global longitudinal strain (RVGLS) and free wall strain (RVFWS) are more sensitive in evaluating RV (dys)function than other functional and hemodynamic parameters in specific populations, such as HF with reduced EF. Purpose: We aimed to assess if endocardial RVGLS, RVFWS, and RV Septal Wall Strain (RVSWS), might have a prognostic and additive value (on top of the conventional measurements) on the outcome of patients with preserved EF. Methods: Retrospective analysis of RV parameters including Peak and End Systolic Strain of RVGLS, RVFWS and RVSWS, RV functional indices (RVFAC% and Machine like TAPSE), Systolic Pulmonary Artery Pressure, in 375 consecutive patients with Preserved Ejection Fraction (EF ≥50%; age 69.1±19; 51% female; Co-morbidity Charlson index 1 (3)). Multivariate Cox regression hazards model was used to determine the association between RV strain parameters to all-cause mortality. Results: RVFWS, RVSWS and RVFAC% were strong predictors of mortality in univariate analysis (HR 1.07 [1.03–1.1]; p≤0.0001, HR 1.08 [1.05–1.12]; p≤0.0001, HR 0.97 [0.95–0.99]; p≤0.0002, respectively). Moreover, after adjustment for clinical (age, gender, Charlson index) and echocardiographic parameters (LA volume, E/e' average, systolic pulmonary pressure), all three parameters remained statistically significant predictors of all-cause mortality (p=0.004, p=0.024, p=0.026, respectively). The best strain univariate predictor of mortality was RVGLS (HR 1.09 [1.05–1.13]; p≤0.0001), being superior to other RV functional indices and systolic pulmonary pressure. Also, after multivariate analysis it remained a statistically significant predictor of mortality (p=0.007). All measurements had good intra-observer and inter-observer reproducibility (Single Measures ICC = 0.90 and ICC = 0.88, respectively). Conclusions: 2DSTE of RVGLS, RVFWS, RVSWS provides significant prognostic value to predict overall mortality in patients with Preserved Ejection Fraction with excellent reproducibility, incremental to routine clinical, hemodynamic and diastolic parameters. Moreover, the strain results of the septal wall showed to be significant, thereover challenging the known hypothesis that the septal wall is mainly influenced by LV function. Funding Acknowledgement: Type of funding source: None